Mengeksplorasi Literasi Digital pada Pembelajaran di Sekolah Dasar - Solih, Mohammad Jabbarudin; Julianto, Indra Rasyid (Jurnal Cahaya Edukasi, 2025)
The digital era demands digital literacy as an essential skill in education, especially in improving the quality of learning in primary schools. Digital literacy not only includes the technical ability to operate technological devices, but also involves skills in searching, assessing, analysing and using information ethically and responsibly. In the context of learning, digital literacy plays a role in increasing students' interest in reading, vocabulary acquisition and critical thinking skills. However, the challenges in its implementation are still considerable, such as low interest in reading, lack of access to digital resources, and limited teacher competence in utilising educational technology. Therefore, the role of teachers is crucial in guiding students to make optimal use of technology. With the support of the right education policy, digital infrastructure development, and improved teacher competence, digital literacy can be an effective means to form a smart, creative and responsible generation in the digital era. This research uses a literature study method and a qualitative approach to analyse various relevant academic sources related to digital literacy in basic education. The literature study was conducted by reviewing various journals, books and research reports that discuss the role of technology in Indonesian language learning in primary schools. The qualitative approach was used to deeply understand how digital literacy affects students' reading interest, vocabulary acquisition and critical thinking skills. With this method, this study aims to provide a comprehensive picture of the challenges and opportunities in implementing digital literacy in the primary education environment.